Dimensions of Job Quality, Mechanisms, and Subjective Well‐Being in the United States1. Issue 2 (4th March 2016) - Horowitz, Jonathan
Abstract : How does job quality predict subjective well‐being in the United States? Prior research suggests that various job quality dimensions such as job security and individual task discretion affect subjective well‐being, but the theoretical mechanisms are implied rather than tested and aspects of job quality are rarely tested together. I use structural equation modeling and General Social Survey data to assess the impact of five job quality dimensions—individual task discretion, monetary compensation, job security, low work intensity, and safe work conditions—on subjective well‐being. Then, I show that job quality influences subjective well‐being by improving social life, altering class identification, affecting physical health, and increasing amounts of leisure time. Finally, while I find that job quality dimensions do have statistically significant effects on subjective well‐being, the way in which job quality affects subjective well‐being differs by job dimension. In other words, job quality has a statistically significant impact on subjective well‐being, but different job quality domains are connected to subjective well‐being in different ways.